An Ethics Journey: From Kant to Assisted Suicide - Gordon, Michael (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Most of us would agree with the almost trite saying that “life is a journey”. Of course it is, unless it ends tragically at birth, and even then it is a very short journey. All of us can describe how we got from one stage in life to another, whether personal, family, education or career. Many journeys seem to be in an almost straight line while others meander from one place to another, changing direction and alternating goals, sometimes zigging back and forth. I have had many wonderful journeys in my life; the choice to change career aspirations from engineering to medicine, the choice the study in medicine in Scotland, the choice to focus on geriatrics and then the choice to branch out into medical ethics to add more depth to clinical medicine. The early undergraduate study of philosophy planted the seed that eventually grew into my completing a Master’s in Medical Ethics; and then expanding my teaching and practice to include palliative care and end of life-decision-making, to most recently participating in the assessment of those requesting medical assistance in dying (MAID in Canada).